Linking atomistic, kinetic Monte Carlo and crystal plasticity simulations of single‐crystal tungsten strength. Issue 2 (September 2015) - Cereceda, David; Diehl, Martin; Roters, Franz; Shanthraj, Pratheek; Raabe, Dierk; Perlado, José Manuel; Marian, Jaime
Abstract Understanding and improving the mechanical properties of tungsten is a critical task for the materials fusion energy program. The plastic behavior in body‐centered cubic (bcc) metals like tungsten is governed primarily by screw dislocations on the atomic scale and by ensembles and interactions of dislocations at larger scales. Modeling this behavior requires the application of methods capable of resolving each relevant scale. At the small scale, atomistic methods are used to study single dislocation properties, while at the coarse‐scale, continuum models are used to cover the interactions between dislocations. In this work we present a multiscale model that comprises atomistic, kinetic Monte Carlo (kMC) and continuum‐level crystal plasticity (CP) calculations. The function relating dislocation velocity to applied stress and temperature is obtained from the kMC model and it is used as the main source of constitutive information into a dislocation‐based CP framework. The complete model is used to perform material point simulations of single‐crystal tungsten strength. We explore the entire crystallographic orientation space of the standard triangle. Non‐Schmid effects are inlcuded in the model by considering the twinning‐antitwinning (T/AT) asymmetry in the kMC calculations. We consider the importance of 〈111〉110 and 〈111〉112 slip systems in the homologous temperature range from 0.08Tm to 0.33Tm, where Tm =3680 K is the melting point in tungsten. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)